LincRNA-Cox2 regulates IL6/JAK3/STAT3 and NF-κB P65 pathway activation in Listeria monocytogenes-infected RAW264.7 cells - Yurong Zhu; Ye Lu; Lin Yuan; Wei Ling; Xugan Jiang; Shengxia Chen; Bing Hu (Elsevier, 2021)
Listeria monocytogenes (Lm) can lead to high mortality rates relative to other foodborne pathogens. Lm-induced inflammation is partly characterized by macrophage activation. Long non-coding RNAs (lncRNAs) have important roles in various biological processes. However, it is unknown how lncRNAs regulate the host response to Lm infection. To identify the role of lncRNA in Lm infection, we used in vitro and in vivo models. We found that lincRNA-Cox2 was highly expressed in Lm-infected RAW264.7 cells. LincRNA-Cox2 knockdown resulted in reduced proinflammatory cytokines, apoptosis, migration ability and enhanced phagocytosis of Lm. LincRNA-Cox2 knockdown also reduced the phosphorylation of Janus kinase 3 (JAK3) and signal transducer and activator of transcription (STAT3) and the nuclear translocation of nuclear factor (NF)-κB P65, which are known to be involved in inflammatory responses. Experimentally inhibiting the protein and phosphorylation levels of STAT3 resulted in reduced proinflammatory cytokines and enhanced phagocytosis of Lm by the RAW264.7 cells. Our research suggests that lincRNA-Cox2 plays important roles in inflammation, the phagocytic function and cell migration ability of RAW264.7 cells by activating interleukin (IL)-6/JAK3/STAT3 signaling, and lincRNA-Cox2 also regulates NF-κB P65 nuclear translocation. Our research provides new insights into the regulatory role of lincRNA-Cox2 in Lm infection.